If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -20 = 8 + 6x Reorder the terms: -20 + 8x = 8 + 6x Solving -20 + 8x = 8 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -20 + 8x + -6x = 8 + 6x + -6x Combine like terms: 8x + -6x = 2x -20 + 2x = 8 + 6x + -6x Combine like terms: 6x + -6x = 0 -20 + 2x = 8 + 0 -20 + 2x = 8 Add '20' to each side of the equation. -20 + 20 + 2x = 8 + 20 Combine like terms: -20 + 20 = 0 0 + 2x = 8 + 20 2x = 8 + 20 Combine like terms: 8 + 20 = 28 2x = 28 Divide each side by '2'. x = 14 Simplifying x = 14
| 3x-14=6+7 | | 120x^3-144x^2+15x-18=0 | | 120x^3-144x^2+15x-84=0 | | 3q-98=2q | | 3v-1=6v-49 | | 5x^4+6x^3+x^2=0 | | 243-3x^2-3y^2=0 | | D/6=(-7) | | 10t-29=7t-17 | | 10+9=3x+34 | | 3x-1/48 | | x+(x+1)=x-1 | | y3/2-1 | | 8x-9=2+5x | | 7x-9=21+5x | | 12e-(19)=7-e | | (9x-3)=(3x+6) | | 6cos(x)+8sin(x)=5 | | y(y-6)=16 | | 5x^2-9=12x | | 7/5x=49 | | 3(6y+7)+7y= | | f(x)=(x-3)(2x+6) | | Ax-3x=5forx | | 8y-(3+4y)= | | m=4Gz | | 4x^2+7=-11x | | Ac-3x=5 | | 9/10()=18 | | 8v^2=56v | | Ax-3x=c | | 7g-15=41 |